Changes in the corrosion rate and microstructure of beta titanium wire using kiwi peel extract - Hilda Fitria Lubis; Hanifa Natarisya (Dental Journal, 2023)
Background: Beta titanium orthodontic wire is known to have good corrosion resistance but is weak in acidic environments, which advance the corrosion rate. One natural inhibitor that can be used to decrease corrosion is kiwi peel extract, which has a high antioxidant level. Purpose: This study aims to examine the ability of the extract to decrease the corrosion rate and microstructural changes of beta titanium at an acidic pH (pH 5). Methods: The samples used were beta titanium with a diameter of 0.016 x 0.022 in and a length of 6 cm. A total of 28 samples (n=28) were divided into four groups—a control group immersed in pH 5 artificial saliva and three treatment groups immersed in kiwi peel extract at concentrations of 400, 500, and 600 ppm (n=7), respectively. The samples were immersed for seven days at 37oC in an incubator. The corrosion rate was tested using the weight-loss method and microstructure change was analyzed using a scanning electron microscope (SEM). Results: One-way ANOVA showed that there are significant differences in corrosion rates between beta titanium immersed in artificial saliva and beta titanium immersed in kiwi peel extract with p=0.01 (p<0.05). SEM analysis results showed that the group with the least surface changes was the one immersed in 400 ppm of kiwi peel extract. Conclusion: Weight-loss and SEM methods show similar results. Kiwi peel extract proved to decrease the corrosion rate and changes in the microstructure of the wire most effectively at a concentration of 400 ppm.